(untitled) (Research, Society and Development, 2022)
Objective: To compare aspects related to the reading of people with aphasia in group speech therapy with patients who did not undergo speech therapy. Method: 27 people with sequelae of aphasia in the subacute phase participated in the research, after the first episode of ischemic stroke: 15 patients who did not undergo speech therapy in a group and 12 who underwent speech therapy in a group. To assess the severity of aphasia, the Boston Diagnostic Aphasia Examination- Reduced (BDAT-R) was applied. A questionnaire was used to assess participants’ reading habits. This assessment in relation to reading was performed at the time of inclusion and after 3 months for both groups. Results: In the comparison of the two groups, there was an increase in the habit of regular reading in the group that underwent speech therapy, although not significant (42% to 75%). The group that did not undergo speech therapy, although not significant, showed a decrease in reading habits after the period (53.3% to 40%), despite having a longer period of schooling. Conclusion: Group speech therapy can allow greater adherence and reading frequency in people with aphasia.